Development of Financial Report Information System as an Effort to Increase MSME Accountability - Libraeni, Luh Gede Bevi; Wijaya, I Ketut Agus Restu (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2025)
Micro, Small, and Medium Enterprises (MSMEs) of painting products have quite diverse financial transaction activities, starting from the purchase of materials, the production process of artworks, to the sale of paintings. However, in practice, MSMEs of painting products generally do not have a structured financial recording and reporting system, so that the financial information generated has not been able to support accountability and optimal business decision making. This research aims to develop a financial reporting information system as an effort to increase accountability in MSMEs of painting products. This research uses an applied research approach with a case study method. Data collection was conducted through interviews, observations, and documentation to identify the current financial recording process and the needs of MSME financial reports. The financial report information system was developed through the stages of needs analysis, system design, implementation, and testing. The resulting system is able to record financial transactions in an integrated manner and produce financial reports in the form of general journals, income statements, balance sheets, cash flow statements, and capital change reports. The results showed that the implementation of the financial report information system was able to improve the process of recording transactions and improve the quality of financial reports of MSMEs of painting products. Financial information becomes more accurate, systematic, and transparent, so that it can support increased accountability and help business owners in making financial decisions. Thus, the development of a financial report information system is an effective solution in supporting the financial governance of MSMEs of painting products.